Propagating lifelong learning culture among educators through web-based training / Dr Wan Zumusni Haji Wan Mustapha - Wan Mustapha, Wan Zumusni (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2018)
Most adults spend a substantial time acquiring information and learning new skills to respond to the rapidity of change, the continuous creation of new knowledge and an ever-widening access to information make such acquisitions necessary. Much of this learning occurs as a result learner's initiative, even if through formal settings. As "knowledge and skills" providers, higher learning institutions must address their institutional role has to keep up the current development by undergoing a change management process, chart new strategic directions, enhance knowledge delivery methods, and increase research and development and industrial linkages. The fact that advances in multimedia and IT have revolutionized the channels through which education is delivered such as using personal computers and video conferencing systems means lectures are now accessible at different places. The advancement of the Internet has allowed the scope of education to be widened and PCs are now viewed as powerful complement to textbooks, and not just the main and sole source of information and reference. At workplace, training is part and parcel of the workers either though directive or voluntarily measures. The infusion of Internet expands lecturers' space and access to greater world of knowledge with the mushrooming of websites offering information on anything they can possibly imagine, known as 'network-based language teaching', where computers are connected to one another in either a local or global network.